Application of the Simplex Lattice Design Methode to Determine the Optimal Formula Nanoemulsion with Virgin Coconut Oil and Palm Oil - Pradita Fiqlyanur Isna Primadana; Tristiana Erawati; Noorma Rosita; Hamdan, Siti Hartini (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: The success of nanoemulsion preparation is characterized by characteristics such as small droplet size, polydispersity index (PDI), and % transmittance, which are close to 100%. One of these factors is the type of oil component used. The Simplex Lattice Design (SLD) method can be used to determine the ratio of oil combinations to obtain an optimal nanoemulsion formula. Objective: The application of the Simplex Lattice Design (SLD) method can help researchers speed up the acquisition of optimal formulas without trial and error so that nanoemulsion formulas that meet specifications can be obtained. Methods: This research uses the Simplex Lattice Design (SLD) method with Design of Expert Version 13 software, with an upper limit value for oil (VCO and Palm Oil) of 2.66% and a lower limit value for oil (VCO and Palm Oil) of 0, which then The results of several formulas come out and characterization testing is carried out to get the best formula from the recommendations produced by the software. Results: The results of the Simplex Lattice Design (SLD) showed that oil affected the droplet size and PDI (p <0.05). Six optimal formulas were obtained, and after testing in the laboratory, there was no significant difference between the results of the SLD program and those of the laboratory (Sig. <0.05). Conclusion: This study shows that the Simplex Lattice Design (SLD) method is very effective.